2019
DOI: 10.26858/est.v5i1.7852
|View full text |Cite
|
Sign up to set email alerts
|

The Use Of 3CM (Cool-Critical-Creative-Meaningful) Model In Blended Learning To Improve Creative Thinking Ability In Solving Mathematics Problem

Abstract: This study aims to describe and test the effectiveness of 3CM learning model with blended learning to improve students' creative thinking ability in solving mathematic problems. A pre experimental design with one group pre-test post-test design pattern was applied in this study. Creative thinking ability is measured by test technique and then in triangulation with observation and interview. Students were given a test, observed when solving the problem, and interviewed based on the answers given. To see the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…Furthermore, research on the application of technology in mathematics curricula, such as STEM has been investigated for various possibilities in the classroom (Lasa et al, 2020). The technology application during the pandemic has made online learning the main choice so that research focuses on e-learning platforms (Farman & Chairuddin, 2020), flipped classrooms, blended learning (Wahyudi et al, 2019), mobile learning, web-based learning (Susanti et al, 2020), and virtual learning (Jatisunda et al, 2020) Cultural factors have essential impacts on the success of learning mathematics. Culturebased mathematical research can be found in traditional house studies (Sulaiman & Nasir, 2020), season systems (Prahmana et al, 2021), traditional community rituals (Nur et al, 2021), and traditional games (Suddin & Deda, 2020).…”
Section: Study Topicsmentioning
confidence: 99%
“…Furthermore, research on the application of technology in mathematics curricula, such as STEM has been investigated for various possibilities in the classroom (Lasa et al, 2020). The technology application during the pandemic has made online learning the main choice so that research focuses on e-learning platforms (Farman & Chairuddin, 2020), flipped classrooms, blended learning (Wahyudi et al, 2019), mobile learning, web-based learning (Susanti et al, 2020), and virtual learning (Jatisunda et al, 2020) Cultural factors have essential impacts on the success of learning mathematics. Culturebased mathematical research can be found in traditional house studies (Sulaiman & Nasir, 2020), season systems (Prahmana et al, 2021), traditional community rituals (Nur et al, 2021), and traditional games (Suddin & Deda, 2020).…”
Section: Study Topicsmentioning
confidence: 99%
“…As Stein (1953) suggests, ‘[t]he creative work is a novel work that is accepted as tenable or useful or satisfying by a group in some point in time’ (311). This definition has been widely employed by creativity researchers (Weisberg, 2015). However, the assessment criteria for creative products have varied (Parkhurst, 1999), generally centring on two criteria: novelty and appropriateness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dengan kesempatan ini, siswa dapat mengembangkan idenya dalam menyelesaikan masalah matematika melalui kegiatan online-offline yang fleksibel. Hal ini sejalan dengan lanjut Wahyudi, et al (2019) mengungkapkan implementasi blended learning dengan salah satu model pembelajaran efektif terhadap kemampuan berpikir kreatif siswa karena pembelajaran ini memberikan kesempatan kepada siswa untuk berpikir secara sistematik, diawali dengan mengkritisi permasalahan kontekstual yang menarik, dan diakhiri dengan refleksi yang bermakna dengan sumber belajar yang memadai baik secara tatap muka maupun online.…”
Section: Gambar 1grafik Perbandingan Ketercapaian Indikator Kemampuan...unclassified